DAMPAK GENDER PADA KARIR: KAJIAN KARIR PLATEAU DAN STRATEGI KARIR - Siti Djamilah (Media Mahardhika, 2021)
This study examined plateau career differences and career strategies between men and women. In addition, this study examines the influence of plateau promotion rules. The research sample was employees in the administration of manufacturing companies in Surabaya and Sidoarjo. Of the 200 questionnaires distributed to employees, who returned 188 questionnaires and only 173 questionnaires that could be used. The next step, the researchers tested the validity and reliability of variables: plateau careers, career strategies and the rule of promotion. Test results show valid and reliable results. Analysis techniques using independent sample t test. In addition, this study uses simple regression analysis techniques to test the effect of the promotion rules on plateau careers. The results of the independent t-test showed that the plateau career between male and female employees was not different. But career strategies between men and women are different. In addition, the results of simple regression indicate that the influence of the promotion rules on plateau careers was supported.